2009
DOI: 10.1002/chem.200801380
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Single‐Molecule Dynamics in Functionalized Mesoporous Silica

Abstract: Mesoporous silica materials are promising host structures for diverse applications in nanoscience. Many applications can profit significantly from the ability to influence guest dynamics in the host matrix. To this end, we introduce covalently attached organic functionalization into the walls of mesoporous silica networks. Using single-molecule fluorescence microscopy, we study the diffusion behavior of single terrylene diimide dye molecules in functionalized mesoporous silica films. We show that, through vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 52 publications
3
34
0
1
Order By: Relevance
“…[416] for a review). In these experiments, luminescent probe molecules were incorporated in as‐synthesized mesoporous silica, and their diffusion along the channels was followed with a fluorescence microscope . The passage of dye molecules between channels was detected, thus proving that the pores were connected .…”
Section: Empty Space Architecturesmentioning
confidence: 99%
“…[416] for a review). In these experiments, luminescent probe molecules were incorporated in as‐synthesized mesoporous silica, and their diffusion along the channels was followed with a fluorescence microscope . The passage of dye molecules between channels was detected, thus proving that the pores were connected .…”
Section: Empty Space Architecturesmentioning
confidence: 99%
“…Angewandte Chemie more, Lebold et al observed that the mobility of TDI molecules can increase or decrease depending on the functional groups attached to the mesoporous silica wall. [59] The authors explained their findings in terms of shielding of the hydroxy groups of the silica surface in combination with changes in the rigidity of the micellar packing in the silica film and directional interactions between the functional groups and the TDI molecules. In summary, single-molecule detection of dye molecules in porous structures reveals a wealth of information about the topology, nanoscale connectivity, and accessibility of the channels of a porous catalyst material.…”
Section: Spatial Heterogeneities In Catalysismentioning
confidence: 99%
“…Single molecule microscopy provides an excellent means to study the effects the functionalization excerts on incorporated guest molecules. 66 Different approaches can be used to influence the mobility of the guest molecule. First, the influence of the functionalization density on the diffusion dynamics of the dye can be examined.…”
Section: Analyzing the Translational Orientational And Spectral Diffmentioning
confidence: 99%
“…66 Fig. 6c shows the diffusion data for aliphatic functional groups with different alkyl chain lengths (methyl, ethyl and propyl).…”
Section: Analyzing the Translational Orientational And Spectral Diffmentioning
confidence: 99%